Sports Traning As Managed Process - Ibragimova Sayyora Babashovna (Euro Asian Journal Publishing, 2023)
Sports training is currently considered as a specialized process of using physical exercises for the purpose of developing and improving qualities and abilities that determine the readiness of athletes to achieve high results in their chosen sport. Understanding sports training as a process presupposes the possibility and necessity of managing this process. The goal of managing the process of sports training is to optimize the behavior of the athlete, the appropriate development of fitness and readiness, ensuring the achievement of the highest sports results
Keywords: sports training; training process; preparedness